PROGNOSIS OF NEUROLOGICAL DISORDERS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Kalbus, O.I.; Makarov, S.O.; Nefodov, O.O. (World of Medicine and Biology, 2024)
The study was devoted to the problem of predicting neurological disorders occurring in patients with systemic lupus erythematosus. Various clinical and paraclinical parameters, such as disease activity, clinical manifestations of the disease, the presence of certain types of antibodies, and so on, have been proposed as possible predictors of the development of neurological disorders in this disease. We performed a comprehensive examination of 64 patients with systemic lupus erythematosus. Based on the obtained results of clinical-neurological, neuropsychological, neuroimaging and immunological studies, we identified the main factors that can be considered predictors of the development of neurological manifestations of systemic lupus erythematosus, the most significant role among which is assigned to antiphospholipid antibodies. Using the obtained data, a predictive model of neurological disorders in patients with lupus was subsequently developed.